Optimasi Fast Disintegrating Tablet Difenhidramin HCl Menggunakan Modifikasi Pati Pisang Kepok Kuning, Crospovidone, dan Microcrystalline Cellulose - Rahmawati, Tias Eka; Siswanto, Agus; Djalil, Asmiyenti Djaliasrin (Faculty of Pharmacy, Universitas Pancasila, 2023)
Diphenhydramine HCl is an antihistamine drug that is available in conventional tablet form. This study aimed to produce the optimum formula for a diphenhydramine fast disintegrating tablet (FDT) using a modification of starch, crospovidone, and microcrystalline cellulose (MCC) to produce quality tablets that meet the tablet's physical requirements and tablet dissolution. Starch modification was made using a two-step method of starch cross-link, then continued with silica coprecipitation. FDT was prepared by the direct compression method. Optimisation with the simplex lattice design (SLD) model uses three components: co-process starch crosslink-silica, crospovidone, and MCC, which obtained 14 formula designs. The hardness, wetting time, disintegration time, and percent dissolution are optimisation parameters. Equations, contour plots, and desirability values were determined as the optimum formula. Based on the research results, an optimum formula was obtained with the proportion of co-process cross-link starch-silica was 56.185 mg, crospovidone at 6 mg, and MCC at 45.815 mg. The result of hardness was 5 kg, wetting time 51.061 seconds, disintegration time 63.129 seconds, and dissolution was 100.972%. The interaction of the three components reduces hardness and increases disintegration time, wetting time, and percent dissolution.